Reaksi Pasar Modal Indonesia Atas Pengumuman Kenaikan Tingkat Suku Bunga Acuan oleh Fed di AS - Rosita Dewi Indra Pratiwi, Kadek; Wirakusuma, I Gede Made (E-Jurnal Akuntansi; Vol 25 No 3 (2018)DO - 10.24843/EJA.2018.v25.i03.p13, 2018)
The purpose of this study was to analyze the Indonesian capital market's reaction to the policy of increasing the benchmark interest rate by the FED (Fed Fund Rate) which was measured using abnormal returns and trading volume activity. The population in this study is all companies listed on the Stock Exchange in 2018 and the research sample was taken using purposive sampling method. Based on the sample selection results according to the criteria, the number of samples used were 45 companies included in the LQ45 stock index.. The analysis technique used in this study is a paired sample t-test. Based on the results of the study, the market reaction is not indicated by the difference in abnormal returns before and after the announcement of the increase in the Fed Fund Rate. However, market reaction is indicated by trading volume activity before and after the announcement of the Fed Fund Rate increase. Keywords: Event study, abnormal return, trading volume activity, interest rate